Undergraduate nursing students' attitudes toward mental health nursing. (August 2015) - Thongpriwan, Vipavee; Leuck, Susan E.; Powell, Rhonda L.; Young, Staci; Schuler, Suzanne G.; Hughes, Ronda G.
Summary: Objectives: The purpose of this study was to describe undergraduate nursing students' attitudes toward mental health nursing and how these attitudes influenced their professional career choices in mental health nursing. Design: A descriptive, online survey was utilized to examine students' perceptions of mental health nursing. A total of 229 junior and senior nursing students were recruited from eight nursing colleges in Midwestern United States to participate in this survey. Results: Students of different ages, genders, ethnicities, and nursing programs did not report significantly different perceptions of: (a) knowledge of mental illness; (b) negative stereotypes; (c) interest in mental health nursing as a future career; and (d), and beliefs that psychiatric nurses provide a valuable contribution to consumers and the community. Negative stereotypes were significantly different between students who had mental health nursing preparation either in class ( p  = 0.0147) or in clinical practice ( p  = 0.0018) and students who had not. There were significant differences in anxiety about mental illness between students who had classes on mental health nursing ( p  = .0005), clinical experience ( p  = 0.0035), and work experience in the mental health field ( p  = 0.0012). Significant differences in an interest in a future career in mental health nursing emerged between students with and without prior mental health experience and between students with and without an interest in an externship program with p -values of 0.0012 and < 0.0001, respectively. Conclusions: The more exposure that students have to mental health nursing through clinical experiences, theory classes, and previous work in the field, the more prepared they feel about caring for persons with mental health issues.